PENGARUH SELF CONGRUITY DAN EXPERIENTIAL VALUE PADA CONSUMER WELLBEING PADA KONSUMEN MAL PARIS VAN JAVA - Kania Kartika, - (2020)
This study aims to determine the effect of self congruity behavior and experiential value on consumer wellbeing in Paris Van Java mall consumers. This research uses a quantitative approach with a correlational method. The sample in this study were 387 Paris Van Java mall consumer respondents. The sampling technique in this study uses incidental sampling. The instrument to measure self congruity behavior is the Self Congruity Instrument compiled by the researcher based on Sirgy's theory (2000), the instrument to measure experiential value is Experiential Value Measurement adapted from research (Sofianti, Irma, 2005), and an instrument to measure consumer well- being is a Consumer Wellbeing to Asians measurement adapted from (Meng et al., 2015). Data analysis techniques used in this study are simple regression analysis to determine the effect of self congruity on consumer wellbeing and multiple regression to determine the effect of self congruity and experiential value on consumer wellbeing. The results of this study indicate that self congruity and experiential value influence consumer wellbeing for Paris Van Java mall consumers.